Social Citizenship And Urban Community Participation - Erna Ermawati Chotim; Ichmi Yani Arinda Rohmah (Eduvest - Journal of Universal Studies, 2024)
Jakarta City as a representation of major city in Indonesia with the highest positive patients infected with covid 19. Various attempts were made by the central and regional governments to break the spread of pandemic covid 19, one of which was to impose Large Scale Social Restrictions (PSBB). However, efforts to overcome government efforts do not seem to be balanced with public awareness to be involved in implementing regulations and to be part of efforts to cope with the spread pandemic covid 19 and recovery. Based on these facts, this study tries to identify the presence or absence of citizenship, the types of citizenship that exist in the people of DKI Jakarta and what efforts can be made to activate citizenship in Jakarta. In the PSBB situation the research method is carried out using a mixed method (quantitative and qualitative) using a questionnaire and in-depth interviews through digital media. The results showed that the type of citizenship that exists in the people of DKI Jakarta at the moment is passive citizenship. However, the results of this study also indicate the potential for community participation that show great potential to build or strengthen social solidarity and capital. It is therefore important to encourage the transformation of activation from passive citizenship into active citizenship including institutional strengthening, so that citizens not only have citizenship rights, but at the same must be obliged to engage in various efforts to overcome the pandemic and recovery after the pandemic occurred.